2022
DOI: 10.1021/acs.accounts.2c00752
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Base–Boryl Radicals Enabled Borylation Reactions and Selective Activation of Carbon–Heteroatom Bonds

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS:The past decades have witnessed tremendous progress on radical reactions. However, in comparison with carbon, nitrogen, oxygen, and other main group element centered radicals, the synthetic chemistry of boron centered radicals was less studied, mainly due to the high electron-deficiency and instability of such 3-center−5-electron species. In the 1980s, Roberts and co-workers found that the coordination of a Lewis base (amines or phosphines) with the boron center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…These results suggest that one equivalent of CyS – acts as a reductant to reduce the ACR-4 ·+ , while the other participates in hydrogen atom transfer (HAT), resulting in the formation of CySSCy (the detailed mechanism is given in Supporting Information). B(OAc) 3 ·– was speculated to possess reductive properties similar to BH 4 ·– and BH 3 CN ·– , and it could potentially be generated in the reaction through HAT between CyS · and BH(OAc) 3 – . In order to investigate the potential of B(OAc) 3 ·– to reduce the trifluoromethyl substrate and generate the gem -difluomethylene radical, cyclohexyl disulfide was employed as an initiator to generate B(OAc) 3 ·– .…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that one equivalent of CyS – acts as a reductant to reduce the ACR-4 ·+ , while the other participates in hydrogen atom transfer (HAT), resulting in the formation of CySSCy (the detailed mechanism is given in Supporting Information). B(OAc) 3 ·– was speculated to possess reductive properties similar to BH 4 ·– and BH 3 CN ·– , and it could potentially be generated in the reaction through HAT between CyS · and BH(OAc) 3 – . In order to investigate the potential of B(OAc) 3 ·– to reduce the trifluoromethyl substrate and generate the gem -difluomethylene radical, cyclohexyl disulfide was employed as an initiator to generate B(OAc) 3 ·– .…”
Section: Resultsmentioning
confidence: 99%
“…During the course of our study on NHC–boryl radical–triggered cascade cyclization reactions ( 41 ), we hypothesized that if a cascade could generate a β-boryl alkyl radical intermediate, β-elimination would take place to liberate the boryl radical, thereby completing a radical catalytic cycle. Furthermore, our previous work had revealed that the regioselectivity of the boryl radical addition to alkynes was tunable by varying the alkynyl substituents ( 45 , 50 ).…”
Section: Reaction Designmentioning
confidence: 99%
“…N -heterocyclic carbene (NHC)–boryl radicals, a class of boron-centered radicals ligated with an NHC component, have shown specific chemical reactivity and have recently found application in chemical synthesis ( 41 , 42 ) since the pioneering work by the groups of Fensterbank, Lacôte, Malacria, and Curran ( 43 ). These radicals can be easily generated from readily available NHC-BH 3 complexes through hydrogen atom abstraction with the aid of a radical initiator ( 43 ).…”
mentioning
confidence: 99%
“…N-Heterocyclic carbene (NHC) complexes of boranes have rapidly emerged as outstanding reagents for synthetic chemistry. [1,2] They are for example highly useful as hydrogen atom donors for radical chemistry, [3,4] or for the radical [5][6][7] or other [8][9][10][11] borylation of substrates, including the initiation of radical polymerizations. [12][13][14][15][16] Recent trends involve transient NHC-boron species that can be used catalytically.…”
Section: Introductionmentioning
confidence: 99%